OZONE AND LASER TREATMENT UNCOMPLICATED ACUTE PURULENT SURGICAL DISEASES OF SOFT TISSUES - A. A. Teuvov; E. I. Soltanov; A. M. Baziev (Кубанский научный медицинский вестник, 2014)
One of the most complex and urgent problems of modern surgery remains the treatment of purulent wounds. Development and improvement of the latest technologies led to wide-scale introduction into clinical practice various methods of physical techniques, which are successfully used in the treatment of the enormous range of diseases. A study of treatment of 253 patients with acute purulent surgery infection without accompanying pathology. Of the 103 patients 1 group in complex treatment included sessions of general and local investigations. In group 2 with 71 patients complex treatment of intravenous laser blood irradiation combined (IV LBI). 3 control group was represented by 79 patients received only traditional complex treatment.